Factors Associated With Withdrawal of Life-Sustaining Therapy After Out-of-Hospital Cardiac Arrest - Michael D. Elfassy, MD, MSc; Mena Gewarges, MD; Steve Fan, PhD; Bianca McLean, MD; Dustin Tanaka, MD; Amrita Bagga, MD; Stephen A. Bennett, MD; Isabella Janusonis, MD; Shamara Nadarajah, MD; Clara Osei-Yeboah, MD; Jeremy Rosh, MD, MSc; Daniel Teitelbaum, MD, MSc; et al. (CJC Open)
Background: Out-of-hospital cardiac arrest (OHCA) is a leading cause of global mortality. Most patients get hypoxic brain injury, which often leads to the withdrawal of life-sustaining therapy (WLST) because of concerns of poor neurologic prognosis. This study describes the rates and reasons for WLST and identifies factors associated with early WLST, defined as occurring within 72 hours of admission. Methods: We conducted a multicentered, retrospective cohort study of adult OHCA patients admitted to 3 large academic hospitals in Toronto from January 2012 to December 2019. Data were extracted from medical records and analyzed using descriptive statistics and cause-specific hazards regression models to identify factors associated with WLST and documented goals of care (GOC) discussions. Results: Among 264 patients (median age 66 years, 76.5% male), the in-hospital mortality rate was 62.1%. Of the nonsurvivors, 67.1% died following WLST (90% of cases because of concern of poor neurologic prognosis), with 50% of WLST occurring <72 hours from admission. Formal declaration of brain death only occurred 9.8% of the time. Older age significantly increased the risk of early WLST. GOC discussions were documented only 56.4% of the time in the overall cohort and significantly associated with WLST across all time periods. Conclusions: This study highlights the high incidence of WLST, and specifically early WLST, in OHCA patients. GOC discussions are routinely undocumented and is associated with a higher likelihood of WLST. These findings underscore heterogeneity of practice, and the influence of GOC discussions in education and shared decision making. Résumé: Contexte: Les arrêts cardiaques survenant hors de l’hôpital sont une des principales causes de mortalité dans le monde. Dans la plupart des cas, les patients subissent des lésions cérébrales hypoxiques, ce qui mène souvent à l’arrêt du traitement de maintien des fonctions vitales (AMFV) en raison d’un pronostic neurologique sombre. Cette étude décrit la fréquence et les motifs de l’AMFV et détermine les facteurs associés à l’AMFV précoce, défini comme survenant dans les 72 heures suivant l’admission à l’hôpital. Méthodologie: Nous avons mené une étude de cohorte rétrospective multicentrique chez des adultes ayant subi un arrêt cardiaque à l’extérieur de l’hôpital qui ont été admis dans trois grands hôpitaux universitaires de Toronto entre janvier 2012 et décembre 2019. Les données proviennent de dossiers médicaux et ont été analysées au moyen de statistiques descriptives et de modèles de régression des risques par cause afin de déterminer les facteurs associés à l’AMFV et les discussions documentées sur les objectifs thérapeutiques. Résultats: Parmi 264 patients (âge médian : 66 ans; 76,5 % d’hommes), le taux de mortalité à l’hôpital était de 62,1 %. Parmi ceux qui n’ont pas survécu, 67,1 % sont décédés après un AMFV (90 % en raison du pronostic neurologique sombre), 50 % des AMFV étant survenus moins de 72 heures après l’admission. Il y a eu une déclaration de mort cérébrale seulement dans 9,8 % des cas. L’âge avancé augmente considérablement le risque d’AMFV précoce. Les discussions sur l’objectif thérapeutique ont été documentées dans seulement 56,4 % des cas dans la cohorte globale et ont été grandement associées à un AMFV à toutes les périodes de temps. Conclusions: Cette étude souligne la fréquence élevée des AMFV, et particulièrement des AMFV précoces, chez les patients subissant un arrêt cardiaque hors de l’hôpital. Les discussions sur les objectifs thérapeutiques ne sont habituellement pas documentées et sont associées à une probabilité accrue d’AMFV. Ces observations soulignent l’hétérogénéité de la pratique et l’influence des discussions sur l’objectif thérapeutique dans l’éducation et la prise de décision conjointe.